FUS-related amyotrophic lateral sclerosis-frontotemporal dementia and links to the DNA damage response: a systematic review - Almalki, Seham; Salama, Mohamed; Taylor, Matthew J.; Ahmed, Zubair; Tuxworth, Richard I. (Frontiers in Molecular Neuroscience, 2025)
Mutations in Fused in Sarcoma (FUS) are associated with neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). This systematic review examined the connections between DNA damage in the central nervous system (CNS), dysfunction of DNA repair processes and the FUS proteinopathy. Twelve peer-reviewed publications were analyzed, investigating this question across a range of models, including immortalized cell lines, ALS-FTD patient-derived induced pluripotent stem cells, mouse tissues and post-mortem samples from ALS-FTD patients. The studies also explored the impact of inducing DNA damage using several agents, including calicheamicin and etoposide, on FUS pathology. Our findings indicated that accumulated DNA damage was documented in all twelve studies, with a key finding being the disruption of interactions between FUS and the DNA damage response (DDR). FUS interactions with various DDR and DNA repair proteins involved in sensing DNA damage and executing the major repair pathways were impaired, resulting in elevated levels of DNA damage in both the nucleus and mitochondria. Therefore, FUS is an essential protein for the preservation of genomic integrity and this loss of genome stability is likely to be a key contributor to the neurodegeneration in ALS-FTD.